The Influence Of Taxpayer Awareness And The Quality Of Fiscal Services On Taxpayer Compliance Taxpayers In Paying Land And Building Tax And Buildings (Pbb) In The Regency Of Deli Serdang - Lestari, Alrida Eka (Al-Adzkiya Publisher, 2024)
Abstract This study aims to determine the effect of taxpayer awareness and the quality of Fiscal Services on taxpayer compliance in paying land and building tax (PBB) in Deli Serdang Regency. The research approach used in this study is an associative quantitative approach. The sampling technique used is Incidental Sampling. Data collection was carried out by distributing questionnaires to land and building taxpayers registered at the Regional Revenue Agency of Deli Serdang Regency. The data analysis technique used in this study is the classical assumption test, multiple linear regression, t test, f test, and the coefficient of determination using the IBM SPSS Version 28.0 program. The results of this study indicate that individually taxpayer awareness has a significant effect on taxpayer compliance in paying land and building taxes, the quality of tax authorities' services has a significant effect on taxpayer compliance in paying land and building taxes. Then simultaneously Taxpayer Awareness and Fiscal Service Quality have a significant effect on Taxpayer Compliance in Paying Land and Building Tax (PBB) in Deli Serdang Regency. Keywords: Taxpayer Awareness, Quality of Taxation Services, Taxpayer Compliance in Paying Land and Building Taxes Abstrak Penelitian ini bertujuan adalah untuk mengetahui Pengaruh Kesadaran Wajib Pajak dan Kualitas Pelayanan Fiskus Terhadap Kepatuhan Wajib Pajak dalam Membayar Pajak Bumi dan Bangunan (PBB) di Kabupaten Deli serdang. Pendekatan penelitian yang digunakan pada penelitian ini adalah pendekatan kuantitatif asosiatif. Teknik pengambilan sampel yang digunakan adalah Sampling Insidental. Pengumpulan data yang dilakukan dengan menyebarkan kuesioner kepada wajib pajak bumi dan bangunan yang terdaftar di Badan Pendapatan Daerah Kabupaten Deli Serdang. Teknik analis data yang digunakan dalam penelitian ini adalah uji asumsi klasik, regresi linear berganda, uji t, uji f, dan koefisien determinan dengan menggunakan program IBM SPSS Versi 28.0. Hasil Penelitian ini menunjukkan bahwa secara persial kesadaran wajib pajak memiliki pengaruh secara signifikan terhadap kepatuhan wajib pajak dalam membayar pajak bumi dan bangunan, kualitas pelayanan fiskus memiliki pengaruh secara signifikan terhadap kepatuhan wajib pajak dalam membayar pajak bumi dan bangunan. Kemudian secara simultan Kesadaran Wajib Pajak dan Kualitas Pelayanan Fiskus berpengaruh signifikan terhadap Kepatuhan Wajib Pajak dalam Membayar Pajak Bumi dan Bangunan (PBB) di Kabupaten Deli serdang